Correlation between a Healty Lifestyle and the Level of Risk Developing Hypertension at the Gateway Sehat Mahulu Primary Hospital - Remon Dian; Wiyadi; Dwi Prihatin Era (PT FORMOSA CENDEKIA GLOBAL, 2023)
Hypertension is referred to as The Silent Killer because it is often without complaints so that sufferers know after complications occur.Aims to determine the relationship between a healthy lifestyle and the level of risk of developing hypertension in patients at the Gateway Sehat Mahulu Hospital.This study used a cross-sectional approach with a non-probability sampling method that was carried out by purposive sampling. obtained 50 respondents who are patients at the Gateway Sehat Mahulu Hospital. This study used a questionnaire about healthy lifestyles and the risk of suffering from hypertension on 21-25 February 2023. Data was analyzed using the chi square test. Using the chi square test, it is known that there is a relationship between a healthy lifestyle and the risk of developing hypertension with a p value of 0.02 (p <0.05).